Randomized controlled trial of late-course concurrent versus sequential chemoradiotherapy after mastectomy and axillary surgery in locally advanced breast cancer. Issue 41 (October 2017) - Lu, Ying; Huang, Haixin; Yang, Hui; Chen, Dagui
Abstract: Background: Concurrent chemoradiotherapy could increase the local control rate in patients with high recurrence risk after breast-conserving surgery, but the effect of concurrent chemoradiotherapy after mastectomy and axillary dissection is not clear. The aim of the study was to compare the effects of late-course concurrent chemoradiotherapy (CCRT) versus sequential therapy (SCRT) after mastectomy and axillary surgery in locally advanced breast cancer. Methods: This was a randomized controlled trial of 155 patients with stage pT3–4p N1–3c M0 or pAnyT pN2–3c M0 breast cancer undergoing 5-fluorouracil+epirubicin+cyclophosphamide followed by docetaxel (FEC-D) chemotherapy after mastectomy and axillary dissection. Patients were randomized to the CCRT group (intensity-modulated radiation therapy was performed concurrently with docetaxel) or to the SCRT group (radiotherapy after chemotherapy). Recurrences, adverse reactions, and short-term effects were observed. Results: All the patients completed the planned therapy. The median follow-up was 39 (range, 16–62) months. Compared with SCRT, the 3-year local-regional recurrence-free survival (LRFS) in the CCRT group was improved (81.8% vs 92.3%, P  = .046). There was no significant difference in 3-year disease-free survival (DFS) and overall survival (OS). In the pT3–4 pN1–3 cM0 subgroup, the 3-year local recurrence-free survival and DFS were significantly improved in the CCRT group (69.4% vs 88.2%, P  = .036; and 41.7% vs 72.6%, P  = .049, respectively). No significant difference was observed adverse reactions between the 2 groups. Conclusion: LRFS of patients with locally advanced invasive breast cancer after mastectomy and axillary surgery was better with CCRT than with SCRT and with similar profiles of adverse reactions. The DFS of patients staged pT3–4 pN1–3 cM0 was also improved.